PENGARUH PERTUMBUHAN EKONOMI, UPAH MINIMUM PROVINSI, DAN TINGKAT PENDIDIKAN TERHADAP PENGANGGURAN TERBUKA DI INDONESIA - Syurifto Prawira (Universitas Negeri Padang, 2018)
This study aims to analyze the effect of economic growth, provincial minimum wage, and education level on open unemployment rate in Indonesia in 2011-2015, either simultaneously or partially. Using panel data with Fixed Efect Model (FEM) approach and using secondary data of 33 provinces in Indonesia. The model estimation results show that the variable of economic growth, provincial minimum wage, and education level simultaneously have significant effect on open unemployment rate in Indonesia. While the partial variable of economic growth has a negative effect but no significant effect on the unemployment rate. The provincial minimum wage variable is partially positive and significant to the unemployment rate. The variable of educational level also have positive and significant effect to unemployment rate. The government is expected to pay serious attention to economic growth, minimum wage system, improving the quality of education, the issue of availability of employment opportunities. Keyword: Economic Growth, Wage, Education, and Unemployment